Development and implementation of a group based mental health intervention for unaccompanied minors. Issue 1 (19th November 2018) - Garoff, Ferdinand; Kangaslampi, Samuli; Peltonen, Kirsi
Abstract : Unaccompanied refugee minors (UMs) are at significant risk to experience severe mental health symptoms (Derluyn, Broekaert & Schuyten). Trauma‐focused treatments have been found to be effective for traumatized refugees (Slobodin & de Jong). However, trauma‐focused mental health services are seldom available, and treatment fails when UMs lack trust in service providers (Majumder, O'Reilly, Karim & Vostanis). In order to address this gap, a 10‐session group based mental health intervention for UMs was developed and then pilot tested in 3 accommodation units for UMs in Finland. The implementation and effectiveness of the intervention was studied by qualitative and quantitative methods. The process was completed by 18 UMs. Symptom measures showed no statistically significant changes on the mental health variables studied. However, staff members and UMs reported increased trust and communication, and participating staff members felt empowered to facilitate groups independently. The group model promoted social interaction and built trust in the accommodation units. Further studies are required to UMs.